Language skills and well-being in early childhood education and care: a cross-sectional exploration in a Swedish context - Riad, Rasmus; Allodi, Mara Westling; Siljehag, Eva; Bölte, Sven (Frontiers in Education, 2023)
Language skills play a vital role in academic achievement and support reading and writing acquisition. Language skills also enable children to interact with others and develop social abilities. Given the predictive value of early language skills for academic attainment and their connection to social interaction, they have been suggested to be an indicator of well-being as well. However, children from culturally and linguistically diverse backgrounds present lower scores than their peers with a majority language background on standardized language tests, such as vocabulary assessment. In the current study, we examined the relationship between language and self-reported well-being in the school context, based on data from a community sample of 85 five-year-old children attending eight preschools in three Swedish municipalities. Language skills was assessed through measures of vocabulary (receptive and expressive) and narrative skills (MAIN) and were analyzed using structural equation modeling. Narrative ability and vocabulary skills were correlated, but they appear to be distinct constructs. Exposure at home to the majority language was positively associated with vocabulary skills, while narrative ability was not strongly associated with language background. Language skills and well-being were not significantly correlated. A novel contribution of this study is empirical data on language performance from a community sample with a large proportion of children with diverse language backgrounds. The relationship between subjective well-being and language skills warrants further investigation.